PENGARUH KOMPOS KULIT BUAH KAKAO TERHADAPPERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI MEDIUM GAMBUT - Mahfudin Mahfudin; Sampoerna Sampoerna; Islan Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this researchis to find out the influence of cocoa pod compost and the best dose on the grounth of cocoa seedling within peat medium. Theresearch was carried out in experimental farmFaculty of Agriculture University of Riau using completely randomized design (CRD).Which consists of 5 treatments and 4 replications.The observations were statistically analyzedfurther testedthe smallest real difference on 5%. Based onresearch results show that the inerease applicationcompost podcocoa give contribution on inereasingparameters seedling height accretion, number of leavesaccretion, leaf area, and seedling dry weight. Whereas parameters trunk circumferenceaccretion, ratio of canopy root get not respon different. Applicationof pod cocoa compostat doses 250g/plant get result supreme at parameters seedling height accretion, number of leaves accretion, trunk circumference accretion,leaf area,ratio of canopy root,seedling dry weight.Keywords : Cocoa Plant, Compost Pod Cocoa, Plant Growth